Development of E-Module Project-Based Learning (PjBL) Plant Diversity Based on the Local Potential of East Sumba Regency to Improve Critical Thinking Skills - Huda, Marleni Rosalia Ndapa; Sari, Murni Sapta; Listyorini, Dwi (BIOEDUKASI, 2024)
This research aims to see the differences in the use of project-based learning e-modules based on the local potential of the East Sumba district on critical thinking skills. This research design uses research by Lee and Owens (2004). The research population was all SMA Negeri 2 Waingapu class X students for the 2023/2024 academic year. The samples were taken in 2 classes, namely 36 students for the experimental class and 36 for the control class. The analysis of critical thinking skills uses the ANCOVA test with a significance level of 5%. Based on the SPSS ANCOVA test output table, a significance value of 0.000 was obtained, which means it is smaller than α 0.05 (Sig < 0.05). This identifies that there are significant differences between classes that use e-modules and those that do not use e-modules. Therefore, it can be concluded that using the E-Module Project-Based Learning (PjBL) Plant Diversity Based on the Local Potential of East Sumba Regency significantly affects students' critical thinking skills.